Scope, strategy and structure: The dynamic of knowledge networks in medicine - Davide Consoli; Ronnie Ramlogan (The University of Manchester, Manchester Business School, 2009)
The objective of this paper is to analyse the dynamics of networks in which new knowledge emerges and through which it is exchanged. Our conjecture is that the structure of a network cannot be divorced from the dynamics of the knowledge underpinning its activities. In so doing we look beyond studies based on the assumption of exogenous networks and delve into the mechanisms that stimulate their creation and transformation. In the first part the paper adopts a functional perspective and views networks as constructs aimed at the coordination of knowledge; accordingly, network structure is an emerging property that reflects the employment of an agreed strategy to achieve a collective scope. In the second part these themes are articulated in relation to the dynamics of medical innovation and enriched by an empirical study on the long-term evolution of medical research in Ophthalmology. This exercise highlights the connection between changes in scientific and practical knowledge and the reconfigurations of the epistemic network over a forty-year period. By mapping different network structures we capture variety in the gateways of knowledge creation that is, the network participants as well as in the pathways that is, the inter-organisational collaborations. Our goal is to analyse how these patterns of interaction emerge and transform over time.
Keywords: 330; innovation; network analysis; inter-organizational relationships; Innovation; Medizin; Forschungskooperation; Soziales Netzwerk; Wissenstransfer